A Monolithic Hybrid Cellulose‐2.5‐Acetate/Polymer Bioreactor for Biocatalysis under Continuous Liquid–Liquid Conditions Using a Supported Ionic Liquid Phase. Issue 44 (10th September 2015) - Sandig, Bernhard; Michalek, Lukas; Vlahovic, Sandra; Antonovici, Mihaela; Hauer, Bernhard; Buchmeiser, Michael R.
Abstract Mesoporous monolithic hybrid cellulose‐2.5‐acetate (CA)/polymer supports were prepared under solvent‐induced phase separation conditions using cellulose‐2.5‐acetate microbeads 8–14 μm in diameter, 1, 1, 1‐tris(hydroxymethyl)propane and 4, 4′‐methylenebis(phenylisocyanate) as monomers as well as THF and n‐heptane as porogenic solvents. 4‐(Dimethylamino)pyridine and dibutyltin dilaurate (DBTDL), respectively, were used as catalysts. Monolithic hybrid supports were used in transesterification reactions of vinyl butyrate with 1‐butanol under continuous, supported ionic liquid–liquid conditions with Candida antarctica lipase B (CALB) and octylmethylimidazolium tetrafluoroborate ([OMIM+][BF4−]) immobilized within the CA beads inside the polymeric monolithic framework and methyl tert‐butyl ether (MTBE) as the continuous phase. The new hybrid bioreactors were successfully used in dimensions up to 2×30 cm (V=94 mL). Under continuous biphasic liquid–liquid conditions a constant conversion up to 96 % was achieved over a period of 18 days, resulting in a productivity of 58 μmol mg−1(CALB) min−1. This translates into an unprecedented turnover number (TON) of 3.9×107 within two weeks, which is much higher than the one obtained under standard biphasic conditions using [OMIM+][BF4−]/MTBE (TON=2.7×106). The continuous liquid–liquid setup based on a hybrid reactor presented here is strongly believed to be applicable to many other enzyme‐catalyzed reactions.